Efektivitas Edukasi Demam Berdarah Dengue terhadap Peningkatan Pengetahuan Ibu-Ibu Dasawisma di Desa Bukit Raya, Kecamatan Sepaku - Sry Reski Mulka; Reza Wahyu Ramadhani; Tsafita Zulfa; Damayanti Ayu Ningtias; Sry Wahyuni; Desti Fauziah Ananta; Bintang Putra Sadewa; Ghufida Arafi; Della Puspita Sari; Enjel Bane Liling; Juniver Veronika Lili (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2025)
Dengue Hemorrhagic Fever (DHF) is an endemic disease in Indonesia, including in Bukit Raya Village, Sepaku Subdistrict, Penajam Paser Utara Regency. Low community knowledge regarding symptoms, prevention, and case reporting may lead to delayed treatment. This activity aimed to improve the knowledge of Dasawisma mothers through health education. The methods included interactive lectures with presentation media, ice breaking, quizzes, and evaluation using pre-test and post-test. Sixteen Dasawisma Pelangi mothers participated in the program. The results showed an increase in the average knowledge score from 44.38 in the pre-test to 74.38 in the post-test. The paired sample t-test revealed a significant difference (p < 0.001). Health education proved effective in improving community knowledge about dengue and is expected to encourage active participation in prevention and early case reporting.